PELATIHAN VIRTUAL TOUR DENGAN PENERAPAN TRANSFER TEKNOLOGI BAGI PEGIAT WISATA - Negara, I.M.K.; Sagita, P.A.W.; Dewi, L.G.L.K.; Juwitasari, W.C.; SWH, Karendra; Diah A, N.P.I. (Buletin Udayana Mengabdi; Vol 24 No 2 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i02.p15, 2024)
The Tourism Awareness Group (Pokdarwis) of Bongan Tourism Village was formed to provide stronger support to the tourism sector. This group exposed a number of obstacles faced, especially in implementing information technology to support the promotion of its tourism products. Partner groups need digital promotion understanding and skills as an alternative step to provide visitors with a better travel experience. As a solution to the obstacles faced by partners, the group offers virtual tour training, replacing the conventional promotional approach that has been used before. The virtual tour plan includes tourist destinations such as beautiful waterfalls, Bali Starling breeding, and Kebo Iwa sites. To overcome partner challenges, the implementation methods applied involve technology transfer as well as evaluation and monitoring. The main target after this activity is to form partners who are able to independently design virtual tours, with the hope of increasing the promotion of tourism villages and having a positive impact on the economy of the local community. Keywords: bongan village, tourist potential, virtual tour.